Clima organizacional en el Ministerio de IncluciónEeconómica y Social Distrito Latacunga durante el período Septiembre2019-Febrero2020. - Acosta Acosta, Jacqueline del Pilar (2020)
The Organizational Environment takes a leading role within both public and private organizations in this sense the Organizational Climate aims to know what is the working environment that surrounds the organization. The present project was developed in Ministerio de Inclusión Económica y Social Distrito Latacunga, in this way to know in what level of Organizational Environment to this Institution, for this, the objective was determining the perception of the Organizational Ministerio de Inclusión Económica y Social Latacunga. The descriptive methodology was applied and the Organizational Environment Scale (EDCO) of (Acero, Echeverri, Lizarazo, Quevedo & Sanabria.2006) was used as a tool, considering (40) items with an evaluation scale from 1 to 5: interpersonal relationships, management style, sense of belonging, Remuneration, Availability of resources, Stability, Clarity and coherence in management and Collective values. The questionnaire was applied in person to 37 administrative officials and 161 operational officials, obtaining a population of 198 respondents from the Ministry of Economic and Social Inclusion during the period September 2019- February 2020. From the analysis of the data, it was identified that in the eight dimensions of the EDCO questionnaire, the officials perceive a good Organizational Climate, reaching a percentage of 82.21% demonstrating that the level of Organizational Climate is high.